2019
DOI: 10.1073/pnas.1912359116
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol shifts gut microbial networks and ameliorates a murine model of neuroinflammation in a sex-specific pattern

Abstract: Alcohol is a widely consumed dietary component by patients with autoimmune neuroinflammatory diseases, but current evidence on the effects of alcohol in these conditions is confounding. Epidemiological studies suggest moderate consumption of alcohol may be protective in some autoimmune diseases; however, this correlation has not been directly investigated. Here, we characterize the effects of moderate-dose alcohol in a model system of autoimmune neuroinflammation, experimental autoimmune encephalomyelitis (EAE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 56 publications
2
33
0
Order By: Relevance
“…In this study, we observed that alcohol consumption increased Prevotella and Parasutterella and decreased Clostridium , Turcibacter and Romboutsia , which is in line with the previous reports [ 46 , 47 , 48 , 49 ]. Moreover, alcohol consumption also increased the abundance of some of the gram-negative bacteria (i.e, Porphyromonadaceae and Alloprevotella ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we observed that alcohol consumption increased Prevotella and Parasutterella and decreased Clostridium , Turcibacter and Romboutsia , which is in line with the previous reports [ 46 , 47 , 48 , 49 ]. Moreover, alcohol consumption also increased the abundance of some of the gram-negative bacteria (i.e, Porphyromonadaceae and Alloprevotella ).…”
Section: Discussionsupporting
confidence: 93%
“…Random blood glucose in obese rats was significantly and negatively correlated with the abundance of Turicibacter ( 61 ). Turicibacter also has immunomodulatory ( 62 ) and inflammation-suppressive ( 63 ) effects. The results of these previous studies are consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…These results motivate further studies to explore the effect of rice beverage on gut microbial communities in a dose-dependent manner. In connection with the emergent reports on the health bene ts of moderate alcohol consumption, this study further opens new dimensions for studying other aspects of consumption of this beverage (Caslin et al 2019;Le Roy et al 2020).…”
Section: Discussionmentioning
confidence: 80%